Estudo etnofarmacológico de produtos naturais utilizados na região do Médio Xingu - VIANA, Pablo de Oliveira (2023)
Ethnopharmacology studies the complex set of relationships between human societies and plants and animals, especially medicines, used in traditional systems of medicine. Through ethnopharmacological studies. it is possible to formulate valuable hypotheses regarding the pharmacological activities of plants and animals cited by a population in a given region. The peoples of the middle Xingu region have a lot of medicinal knowledge built up over centuries of interaction with the Amazon rainforest. Therefore, this research aims to carry out an ethnopharmacological survey of natural products used in the Middle Xingu region, and to describe the uses of medicinal plants and biologically active principles derived from animals, and to create a database of the medicinal uses of the products. natural (plants). The work is a prospective study, starting from the ethnopharmacological survey of natural products used by residents of the cities of Altamira, Anapú, Brasil Novo, Senador José Porfírio and Vitória do Xingu (average Xingu). The study population was composed of riverside, urban and rural, peoples of the region who make use of folk and traditional medicine. Data collection was carried out from November 2019 to February 2020, through interviews, group discussions with knowledgeable people and meetings with practitioners of medicinal therapies, in which two questionnaires were applied to users of medicinal therapies. Based on the results of the research, it was noticed that the valorization of ethno-knowledge in relation to the therapeutic properties of plants and popular knowledge have proved to be a strong supporter of technical- scientific knowledge. It is also seen that the recovery of degraded environments will allow for an improvement in water quality, reduction of erosion, food for fauna and flora, as well as a refuge for the biodiversity of medicinal plants and conservation of traditional knowledge derived from nature, in addition to seeking register and value the medicinal therapeutic culture of the traditional peoples of this Amazon region.